Evaluation of Hospital Service Quality with the SERVQUAL Method Approach and Quality Function Deployment (QFD) - Tika Kristianti; Sayid Bahri Sriwijaya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Quality hospital services are the main demand in the modern era that prioritizes patient satisfaction as the main indicator of the success of health services. This study aims to evaluate the quality of hospital services using a combined approach between the SERVQUAL and Quality Function Deployment (QFD) methods. The research was conducted qualitatively using in-depth interview techniques and participatory observation at one of the referral hospitals in Banten Province. The SERVQUAL method was used to identify gaps between patient expectations and perceptions of five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results showed that the responsiveness and empathy dimensions had the most significant gaps, indicating the need for improvement in the aspects of service speed and attention to patients. Furthermore, the QFD method was applied to translate patient needs into technical specifications of hospital services through the preparation of the House of Quality (HOQ). Some of the key patient needs identified included improving the quality of staff communication, waiting room comfort, and utilization of digital service systems. The literature review supports that the combined approach between SERVQUAL and QFD is able to produce solutions that are applicable and oriented towards systemic improvement of health services. This research makes an important contribution to hospital management in designing strategies based on patient needs as well as a reference for sustainable service development. The results also highlight the important role of service innovation in improving hospital competitiveness at the regional level.